An Analysis of he Role of the Internal Audit Function in Enterprise Wide Risk Management: a Case of Communications and Allied Industries Pension Fund - Musiyazviriyo, Arnold (Midlands State University, 2017)
The study aims to demonstrate the role of internal audit as a pillar of support for management in enterprise wide risk management. The performance of an internal audit department must function in a manner that is in accordance with applicable professional standards such as Standards for the Professional Practice of Internal Auditing (SPPIA, 2009) and the quality of the internal control systems. The involvement of internal audit in risk management has gained wide attention in the years from 2008 due to the public scandals which were mainly caused by the world recession. The attention of internal audit with regards to risk management increased which resulted in many internal auditors adopting a risk based audit approach, neglecting the traditional control based approach. This projects however did not intend to explain the reason for the change from control based to risk based but tried to analyse the role of internal auditing in the management of organizational risk. Reference was given to the case of Communication and Allied Industries Pension Fund which has an internal audit that is involved in enterprise wide risk management. The data collection method in this research used both qualitative and quantitative method to achieve the fore mentioned objective. The major findings of this research indicated that default, credit and liquidity risk are the main risks that threatens the operations of the pension fund. It was also revealed that the risk appetite of the pension fund was low as compared to the economic activities of the same.